Asset Recovery Mechanism for Victims of Illegal Investment Fraud : “A Comparative Study of Indonesia and Malaysian Law (Analysis of the Binomo Case Decision) - Efika Weny Meida Simatupang; Ranisa Diati; Slamet Tri Wahyudi; Supardi Supardi (Fakultas Hukum Dehasen, 2026)
Illegal investment fraud through binary option platforms such as Binomo has caused massive financial losses to thousands of victims in Indonesia. This study aims to analyze the asset recovery mechanism for victims of illegal investment fraud within the Indonesian legal system based on an analysis of the Binomo case verdict, and to compare it with the asset recovery mechanism under Malaysian law. This research employs a normative legal research method with statutory, case-based, and comparative approaches. The findings indicate that Indonesian law has provided asset recovery mechanisms through restitution, joinder of compensation claims in criminal proceedings, and asset forfeiture under the Anti-Money Laundering Law; however, their implementation remains inconsistent, as reflected in the Binomo case rulings. In contrast, Malaysia through AMLATFPUAA 2001 offers a more comprehensive framework, including civil forfeiture without requiring full criminal conviction. This study recommends the adoption of a non-conviction based forfeiture mechanism and the establishment of a dedicated asset management institution in Indonesia as a strategic step toward legal reform.